Efektivitas Pelatihan Dzikir dalam Meningkatkan Ketenangan Jiwa pada Lansia Penderita Hipertensi - Olivia Dwi Kumala; Yogi Kusprayogi; Fuad Nashori (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
This study aims to determine whether there is a decrease in blood pressure and an increase in peace of soul after dhikr training being given to the elderly who suffer from hypertension. Subjects in this study were 9 elderly female people with the age range of 55-70 years. The method used in this research was experimental with pretest and posttest models. Training was conducted in 7 sessions. Measurements were performed before training (prettest) and after the training ended (posttest). Then the data was analyzed by Wilcoxon rank test using SPSS 16. Based on the data analysis, hypothesis test scores were Z = -2.627 and p = 0.008 (p <0.05). These results indicated a significant difference between the level of peace of soul in the delivery of training before and after training sessions.